The Danger of Domestic Pre-Conceived Views with Respect to the Uniform Interpretation of the CISG: The Question of Avoidance In the Case of Non-Conforming Goods and Documents - Schwenzer, Ingeborg (Victoria University of Wellington Law Review, 2019)
Professor Schwenzer compares common law notions about a party's ability to avoid a sales contract with the position under article 49 of the Convention on the International Sale of Goods. Having noted that the approach of the CSIG has given rise to criticism, she then argues that such criticism is unfounded and that, moreover, the CSIG's provisions reflect the reality of international sales practice and case law.